PENGARUH SISTEM INFORMASI SUMBER DAYA MANUSIA, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN SITUBONDO - Karnadi Karnadi; Ediyanto Ediyanto (Relawan Jurnal Indonesia, 2021)
This study aims to (1) to determine the effect of Human resource information system, Competence and Work discipline partially to performance of ASN (2) to determine the effect of Human resource information system, Competence and Work discipline simultaneously to Performance of ASN (3) to find out which one the variables of Human resource information system, Competence and Performance of ASN. The research method used in this thesis is a quantitative method. The result of research in multiple linear regression analysis, namely Y = 6.787 + 0.754X1 - 0.243X2 + 0.359 X3 + e. Partially Human resource information system has significant postive effect with a tcount value of 7,915 ttable of 2.001, Competence has not significant positive effect with a tcount of -1,636 ttable of 2.001 and Work discipline has significant positive effect with a tcount of 2,103 ttable of 2.001. Simultaneously the Human resource information system, Competence and Work discipline affect the performance of ASN with an Fcount of 63,522 Ftable of 2.76. The dominant variable in this study is the Human resource information system with a value of 7,915.